EXPRESSION OF THE FLUORESCENT PROTEIN MTURQUOISE2 IN THE PERIPLASM OF Escherichia coli - Handayani, Ira; Kusharyoto, Wien (LIPI Press, 2016)
Many variants of cyan fluorescent protein (CFP) have been developed as fluorescent tags which are widely used as donors in Förster resonance energy transfer (FRET) experiments. Recent improvement of CFP variants resulted in mTurquoise2, a brighter variant with faster maturation, high photostability, longer mono-exponential lifetime and the highest quantum yield measured for a monomeric fluorescent protein. Here, the authors describe the expression of mTurquoise2 targeted for secretion via the general secretory (Sec) translocation pathway into the highly oxidizing periplasm of Escherichia coli. The use of signal peptide MPB*1, a modified signal sequence of maltose binding protein was investigated. The His6-tagged fluorescent protein was expressed in E. coli NiCo21(DE3) and purified by means of immobilized metal ion affinity chromatography (IMAC) on TALON™ matrix. In SDSPAGE and Western blot analysis, a single band corresponding to a molecular mass of approximately 28 kDa was observed, which correlated with the predicted molecular mass based on the amino acid sequence of mTurquoise2.